2021
DOI: 10.1021/acsbiomaterials.1c00067
|View full text |Cite|
|
Sign up to set email alerts
|

Noncovalent Functionalized Graphene Nanocarriers from Graphite for Treating Thyroid Cancer Cells

Abstract: Here, biocompatible graphene (G) nanocarriers decorated with iron oxide nanoparticles (IONPs) were prepared using 2-(methacryloyloxy)ethyl phosphorylcholine (MPC) and poly(ethylene glycol) monomethacrylate (PEGMA). For this, we report the use of graphite directly instead of graphene oxide or reduced graphene oxide. Graphene nanocarrier (in situ GIOPMPC) was prepared in one-pot by in situ copolymerization of MPC and PEGMA monomers in the presence of IONPs and G. GIOPMCP nanocarriers were prepared by sonication … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 59 publications
0
6
0
Order By: Relevance
“…GIOPMPC alone has been shown to have negligible toxicity; however, significant toxicity was observed via effects on apoptosis, cell proliferation, and DNA damage when loaded with DOX. 158 Besides focused drug delivery and long-lasting circulation time, steady drug release (consistent medication release) is of paramount importance for a nanocarrier to act efficiently. Farahani et al 159 designed a graphene-based nanocarrier stabilized with BSA, decorated with chitosan, and grafted with DOX.…”
Section: Drugs Used In Cancer Chemotherapymentioning
confidence: 99%
“…GIOPMPC alone has been shown to have negligible toxicity; however, significant toxicity was observed via effects on apoptosis, cell proliferation, and DNA damage when loaded with DOX. 158 Besides focused drug delivery and long-lasting circulation time, steady drug release (consistent medication release) is of paramount importance for a nanocarrier to act efficiently. Farahani et al 159 designed a graphene-based nanocarrier stabilized with BSA, decorated with chitosan, and grafted with DOX.…”
Section: Drugs Used In Cancer Chemotherapymentioning
confidence: 99%
“…As nanoparticles, GO is considered as a novel nanoreagent for cancer treatment . GO has great application prospects in cancer treatment, which has attracted wide attention in multidisciplinary fields . It was reported that the effect of GO was involved in cell apoptosis of breast cancer cells .…”
Section: Introductionmentioning
confidence: 99%
“…10 GO has great application prospects in cancer treatment, which has attracted wide attention in multidisciplinary fields. 11 It was reported that the effect of GO was involved in cell apoptosis of breast cancer cells. 12 GO could cause dose-dependent toxicity of breast cancer cells by analysis of cell viability.…”
Section: ■ Introductionmentioning
confidence: 99%
“…This polymer was prepared from the 2-(methacryloyloxy)ethyl phosphorylcholine monomer by free radical polymerization. PMPC is a biocompatible polymer and is used widely in bioapplication, enriched with nitrogen, phosphorus, and oxygen [ 45 , 46 ]. Since PMPC has heteroatoms it was believed that CDs from this polymer will exhibit excellent optical properties with low toxicity.…”
Section: Introductionmentioning
confidence: 99%